KEEFEKTIFAN MODEL INKUIRI TERBIMBING BERBANTUAN VIDEO INTERAKTIF TERHADAP KEMANDIRIAN BELAJAR SISWA KELAS V SD NEGERI JATIJAJAR - Bunga Septiana Sari; Kartika Yuni Purwanti (Smart Education, 2025)
Abstract: The aim of this study was to ascertain whether the guided inquiry model, with the aid of interactive video, increased the level of learning independence among grade V students at SDN Jatijajar 01. This study was designed using a quasi-experimental methodology. With samples of grade V students from SDN Jatijajar 01 and SDN Jatijajar 02, the study's population consisted of SDN Jatijajar students. Questionnaires, observation sheets, unstructured interviews, and documentation were among the methods utilized to collect data. The Normality Test, Homogeneity Test, Independent Sample T-test, Simple Linear Regression Test, and Paired Sample T-test were among the data analysis methods employed. The findings of this investigation show that: (1) With the help of interactive videos, students' learning independence varies in the guided inquiry approach. H0 is rejected while Ha is accepted based on the Independent Sample T-test findings, which indicate a significance value of 0.001 <0.05. (2) Students' learning independence is impacted by the guided inquiry model with interactive video assistance. The significance value, which is 0.001 <0.05, indicates that Ha is accepted and H0 is rejected. (3) Using guided inquiry models with the use of interactive films increases students' learning freedom. With a significant value of 0.001 <0.05 from the paired sample t-test, Ha is accepted and H0 is denied. It is clear that the interactive video-assisted guided inquiry methodology works well to help pupils at Jatijajar 01 State Elementary School become more independent learners. Keyword: Guided Inquiry; Interactive Video; Learning Independence. Abstrak: Tujuan penelitian adalah untuk mengidentifikasi tingkat kemandirian belajar yang meningkat melalui penggunaan model inkuiri terbimbing berbantuan video interaktif oleh siswa kelas V di SDN Jatijajar 01. Penelitian ini dilakukan dengan populasi siswa SDN Jatijajar, dengan sampel siswa kelas V dari SDN Jatijajar 01 dan SDN Jatijajar 02. Desain penelitian ini adalah Quasi Eksperimen. Angket, wawancara tidak terstruktur, lembar observasi, dan dokumentasi adalah metode pengumpulan pada data. Analisis data juga menggunakan uji normalitas, homogenitas, uji sampel T bebas, uji regresi pada linier sederhana, dan uji sampel T berurutan. Penelitian ini menemukan bahwa: (1) Terdapat perbedaan dalam kemandirian belajar siswa dalam model inkuiri terbimbing berbantuan video interaktif. Hasil Uji Sampel pada Independen T juga menunjukkan bahwa nilai signifikansi 0.001 di bawah 0,05 menunjukkan bahwa H0 ditolak dan Ha diterima, (2) Terdapat juga pengaruh model inkuiri pada terbimbing berbantuan video interaktif terhadap kemandirian belajar siswa, dan (3) Terdapat peningkatan dalam kemandirian belajar siswa dalam model inkuiri terbimbing berbantuan video interaktif. Dengan nilai signifikansi 0.001 < 0,05, uji sampel ganda t menunjukkan bahwa H0 ditolak dan Ha juga diterima. Model inkuiri terbimbing berbantuan video interaktif meningkatkan kemandirian belajar siswa SD Negeri Jatijajar 01. Kata kunci: Inkuiri Terbimbing; Video Interaktif; Kemandirian Belajar.